Heat-conducting insulating spacer as well as preparation method and application thereof

By combining the preparation and use of double-ended vinyl silicone oil, hydrogen-containing silicone oil and other materials, as well as inorganic thermal conductivity powders such as submicron single crystal aluminum oxide and aluminum nitride fiber, the existing thermal conductivity insulating gaskets have low thermal conductivity and poor tear strength. Problem, thermally conductive insulating gaskets with high thermal conductivity, high tear strength and insulation are achieved.

CN119432092APending Publication Date: 2025-02-14DONGGUAN HANPIN ELECTRONIC CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411812116.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The thermal conductivity of existing thermal insulation gaskets is relatively low and cannot meet applications with higher thermal conductivity requirements. At the same time, high filling amount leads to poor tearing and easy tearing; while the addition of carbon fiber leads to poor insulation performance.

Method used

Use double-ended vinyl silicone oil, hydrogen-containing silicone oil, inhibitors, long-chain silane coupling agents, catalysts, submicron single crystal alumina, aluminum nitride fibers, spherical alumina and diamond powder for compound preparation to form a thermally conductive insulating pad piece.

Benefits of technology

The combination of high thermal conductivity, high tear strength and insulation is achieved, making the thermally conductive insulating gasket not easy to tear, is suitable for thinner sheets, and shows good performance in areas with high thermal conductivity requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005180792750000141
    Figure BDA0005180792750000141
  • Figure BDA0005180792750000151
    Figure BDA0005180792750000151
Patent Text Reader

Abstract

The invention provides a heat-conducting insulating spacer as well as a preparation method and application thereof. The heat-conducting insulating spacer is prepared from the following raw materials in parts by weight: 23 to 30 parts of double-end vinyl silicone oil, 1 to 4 parts of hydrogen-containing silicone oil, 0.05 to 0.2 part of alkynol inhibitor, 1 to 6 parts of long-chain silane coupling agent, 0.1 to 0.5 part of platinum catalyst, 80 to 160 parts of submicron single crystal aluminum oxide, 60 to 180 parts of aluminum nitride fiber, 300 to 400 parts of spherical aluminum oxide and 280 to 480 parts of diamond powder. The heat-conducting insulating spacer provided by the invention has the characteristics of high heat conductivity coefficient, high tearing strength and insulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal conductive materials, and in particular relates to a thermal conductive insulating gasket and a preparation method and application thereof. Background Art

[0002] As microelectronic devices become more and more integrated, their waste heat problem has become a key issue restricting the development of the industry. The waste heat of electronic devices causes the device temperature to rise, which will reduce system stability, affect device performance, and shorten the device life. Thermal pads, as a device used to increase the thermal conductivity between heat sources and cold sources, are widely used in the field of electronics and electrical engineering to solve the waste heat problem of electronic devices.

[0003] CN117924776A discloses a heat-conducting silicone gasket and a preparation method thereof, wherein the heat-conducting silicone gasket comprises a polyimide film and a heat-conducting material layer, wherein the heat-conducting material layer comprises the following components in parts by weight: 15-30 parts of methyl vinyl silicone rubber, 3-10 parts of hydrogen-containing silicone oil, 1-3 parts of platinum catalyst, 40-50 parts of modified alumina, 20-35 parts of modified hexagonal boron nitride, 2-5 parts of vulcanizing agent and 0.5-2 parts of inhibitor; wherein the modified alumina is alumina surface-modified by a silane coupling agent, and the modified hexagonal boron nitride is hexagonal boron nitride modified by hexadecyltrimethylammonium bromide. The heat-conducting silicone gasket prepared by this technical solution has the characteristics of high thermal conductivity and low hardness, but its thermal conductivity is low and cannot meet the application in fields with higher thermal conductivity requirements.

[0004] CN114539779A discloses a carbon fiber silicone gasket with high thermal conductivity and ultra-high temperature resistance and a preparation method thereof. The carbon fiber silicone gasket with high thermal conductivity and ultra-high temperature resistance comprises, by weight, 15 to 35 parts of organic solvent, 5 to 12 parts of silicone rubber, 1 to 5 parts of silicone oil, 1 to 3 parts of reinforcing agent, 0.2 to 0.5 parts of coupling agent, 10 to 25 parts of carbon fiber, 40 to 60 parts of thermal conductive filler, 0.5 to 1.5 parts of cross-linking agent, 0.1 to 0.3 parts of thixotropic agent, 0.02 to 0.05 parts of acetylene alcohol inhibitor and 0.1 to 0.5 parts of platinum catalyst. The carbon fiber silicone gasket with high thermal conductivity and ultra-high temperature resistance provided by the technical solution has good mechanical properties and high thermal conductivity, but the addition of carbon fiber leads to a decrease in resistivity and a deterioration in insulation performance, which limits its application in fields requiring insulation and thermal conductivity.

[0005] In the prior art, the thermal conductivity of insulating thermally conductive gaskets is relatively low and cannot meet the application requirements of fields with higher thermal conductivity. At the same time, when the thermal conductive powder filling amount is very high, the tear strength deteriorates significantly and is easy to tear, which limits its operation and application. Although the thermal conductive gasket filled with carbon fiber has a high thermal conductivity, it does not have insulation properties, which limits its application.

[0006] Therefore, it is necessary to develop a thermally conductive insulating gasket with high thermal conductivity, high tear strength and insulation. Summary of the invention

[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a thermally conductive insulating gasket and a preparation method and application thereof, wherein the thermally conductive insulating gasket has the characteristics of high thermal conductivity, high tear strength and insulation.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a thermally conductive insulating gasket, wherein the raw materials for preparing the thermally conductive insulating gasket include the following components in parts by weight: 23 to 30 parts (for example, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts or 29 parts) of double-ended vinyl silicone oil, 1 to 4 parts (for example, 1.5 parts, 2 parts, 2.5 parts, 3 parts or 3.5 parts) of hydrogen-containing silicone oil, 0.05 to 0.2 parts (for example, 0.07 parts, 0.09 parts, 0.11 parts, 0.13 parts, 0.15 parts, 0.17 parts or 0.19 parts), 1 to 6 parts (for example, 2 parts, 3 parts, 4 parts or 5 parts) of a long-chain silane coupling agent, and 0.1 to 0.5 parts (for example, 0.15 parts, 0.2 parts, 0.3 parts, 0.35, 0.4 or 0.45 parts, etc.), 80-160 parts (for example, 90, 100, 110, 120, 130, 140 or 150 parts, etc.) of submicron single crystal alumina, 60-180 parts (for example, 80, 100, 120, 140 or 160 parts, etc.) of aluminum nitride fibers, 300-400 parts (for example, 310, 320, 330, 340, 350, 360, 370, 380 or 390 parts, etc.) of spherical alumina, and 280-480 parts (for example, 300, 320, 340, 360, 380, 400, 420, 440 or 460 parts, etc.) of diamond powder.

[0010] In the present invention, the double-terminal vinyl silicone oil as a matrix resin can react chemically with hydrogen-containing silicone oil to generate a polymer network; the submicron single crystal alumina, aluminum nitride fiber, spherical alumina and diamond powder as inorganic thermal conductive powder can improve the thermal conductivity; the aluminum nitride fiber can not only help to improve the thermal conductivity, but also improve the mechanical strength and toughness of the thermal conductive insulating gasket, increase the tear strength, and make the thermal conductive insulating gasket not easy to be torn, even if it is a thin sheet of 0.3 to 0.8 mm, it can be well operated and used. The long-chain silane coupling agent can improve the compatibility of inorganic thermal conductive powder with double-terminal vinyl silicone oil and hydrogen-containing silicone oil, promote the dispersion of inorganic thermal conductive powder, and thus play a better thermal conductive role. The catalyst can catalyze the chemical reaction between double-terminal vinyl silicone oil and hydrogen-containing silicone oil; the inhibitor can inhibit the catalytic effect of the catalyst, and it will volatilize at high temperature, thereby losing the inhibitory effect, so that the reaction can proceed. The raw materials used in the preparation of the thermal conductive insulating gasket are all insulating, so the prepared thermal conductive insulating gasket has good insulation.

[0011] Preferably, the hydrogen-containing silicone oil includes double-ended hydrogen-containing silicone oil and side hydrogen-containing silicone oil.

[0012] In the present invention, the double-terminal hydrogen-containing silicone oil and the side hydrogen-containing silicone oil are used as a chain extender and a cross-linking agent respectively, and can chemically react with the double-terminal vinyl silicone oil to generate a macromolecular network structure, so that the thermally conductive insulating gasket has good mechanical properties.

[0013] Preferably, the mass ratio of the double-ended hydrogen-containing silicone oil to the side hydrogen-containing silicone oil is 1:(2.8-3.2), for example, 1:2.85, 1:2.9, 1:2.95, 1:3, 1:3.05, 1:3.1 or 1:3.15, etc.

[0014] Preferably, the inhibitor comprises an alkynol inhibitor.

[0015] Preferably, the long-chain silane coupling agent includes n-decyltrimethoxysilane and / or dodecyltrimethoxysilane.

[0016] Preferably, the catalyst comprises a platinum catalyst.

[0017] Preferably, the D50 particle size of the submicron single crystal alumina is 0.4-0.6 μm, for example, 0.42 μm, 0.44 μm, 0.46 μm, 0.48 μm, 0.50 μm, 0.52 μm, 0.54 μm, 0.56 μm or 0.58 μm.

[0018] In the present invention, the intrinsic thermal conductivity of the submicron single crystal alumina is higher than that of ordinary alumina, which can reach 35 to 40 W / (m·K). The D50 particle size of the submicron single crystal alumina is preferably 0.4 to 0.6 μm, which can fill the gaps between large-particle inorganic thermal conductive powders to form more thermal conductive networks and improve the thermal conductivity.

[0019] Preferably, the aluminum nitride fiber has a diameter of 5 to 20 μm (for example, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm, 17 μm or 19 μm, etc.) and a length of 1 to 3 mm (for example, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm, 2.0 mm, 2.2 mm, 2.4 mm, 2.6 mm or 2.8 mm, etc.).

[0020] In the present invention, the intrinsic thermal conductivity of the aluminum nitride fiber can reach 180 to 320 W / (m·K). Adding aluminum nitride fiber and compounding with other components can give the thermally conductive insulating gasket high thermal conductivity, high tear strength and high toughness.

[0021] Preferably, the spherical alumina comprises a combination of a first spherical alumina, a second spherical alumina and a third spherical alumina, the D50 particle size of the first spherical alumina is 2 to 8 μm (for example, 3 μm, 4 μm, 5 μm, 6 μm or 7 μm, etc.), the D50 particle size of the second spherical alumina is 35 to 55 μm (for example, 37 μm, 39 μm, 41 μm, 43 μm, 45 μm, 47 μm, 49 μm, 51 μm or 53 μm, etc.), and the D50 particle size of the third spherical alumina is 80 to 130 μm (for example, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm or 125 μm, etc.).

[0022] Preferably, the mass ratio of the first spherical alumina, the second spherical alumina and the third spherical alumina is 1:(0.5-3):(1-5), for example, 1:1:2, 1:1:3, 1:1:4, 1:2:2, 1:2:3 or 1:2:4, etc.

[0023] Preferably, the diamond powder comprises a combination of a first diamond powder, a second diamond powder and a third diamond powder, the first diamond powder has a D50 particle size of 5 to 10 μm (for example, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm or 9.5 μm, etc.), the second diamond powder has a D50 particle size of 20 to 45 μm (for example, 23 μm, 26 μm, 29 μm, 32 μm, 35 μm, 38 μm, 41 μm or 44 μm, etc.), and the third diamond powder has a D50 particle size of 90 to 150 μm (for example, 100 μm, 110 μm, 120 μm, 130 μm or 140 μm, etc.).

[0024] Preferably, the mass ratio of the first diamond powder, the second diamond powder and the third diamond powder is 1:(0.5-3):(1-5), for example, 1:1:2, 1:1:3, 1:1:4, 1:2:2, 1:2:3 or 1:2:4.

[0025] Preferably, the raw materials for preparing the thermally conductive insulating gasket also include color paste.

[0026] In the present invention, the desired color can be given to the thermally conductive insulating gasket by adding color paste.

[0027] Preferably, the weight proportion of the color paste in the raw materials for preparing the thermally conductive insulating gasket is 0.1 to 1 part, for example, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part or 0.9 part, etc.

[0028] Preferably, the thickness of the thermally conductive insulating gasket is 0.3-10 mm, for example, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm or 9 mm.

[0029] In a second aspect, the present invention provides a method for preparing a thermally conductive insulating gasket as described in the first aspect, the preparation method comprising the following steps: kneading, calendering, and vulcanizing double-ended vinyl silicone oil, hydrogen-containing silicone oil, an inhibitor, a long-chain silane coupling agent, a catalyst, submicron single crystal alumina, aluminum nitride fiber, spherical alumina, and diamond powder to obtain the thermally conductive insulating gasket.

[0030] Preferably, the preparation method specifically comprises the following steps:

[0031] (1) A double-terminal vinyl silicone oil, a hydrogen-containing silicone oil, an inhibitor, a long-chain silane coupling agent and a catalyst are subjected to a first kneading and a second kneading to obtain a first mixture.

[0032] (2) The first mixture obtained in step (1), submicron single crystal alumina, aluminum nitride fiber, first spherical alumina and first diamond powder are subjected to first kneading and second kneading to obtain a second mixture.

[0033] (3) The second mixture obtained in step (2), the second spherical alumina, and the second diamond powder are subjected to first kneading and second kneading to obtain a third mixture.

[0034] (4) The third mixture obtained in step (3), the third spherical alumina, the third diamond powder and optionally the color paste are subjected to a first kneading and a second kneading to obtain a fourth mixture.

[0035] (5) Calendering and vulcanizing the fourth mixture obtained in step (4) to obtain the thermally conductive insulating gasket.

[0036] Preferably, the kneading frequency of the first kneading in step (1) is 25-35 Hz (for example, 26 Hz, 27 Hz, 28 Hz, 29 Hz, 30 Hz, 31 Hz, 32 Hz, 33 Hz or 34 Hz, etc.), and the kneading time of the first kneading is 5-10 min (for example, 5.5 min, 6 min, 6.5 min, 7 min, 7.5 min, 8 min, 8.5 min, 9 min or 9.5 min, etc.).

[0037] Preferably, the second kneading in step (1) is carried out under vacuum, the kneading frequency of the second kneading is 25-35 Hz (for example, 26 Hz, 27 Hz, 28 Hz, 29 Hz, 30 Hz, 31 Hz, 32 Hz, 33 Hz or 34 Hz, etc.), and the kneading time of the second kneading is 5-10 min (for example, 5.5 min, 6 min, 6.5 min, 7 min, 7.5 min, 8 min, 8.5 min, 9 min or 9.5 min, etc.).

[0038] Preferably, the kneading frequency of the first kneading in step (2), step (3) and step (4) is independently 12 to 18 Hz (for example, 13 Hz, 14 Hz, 15 Hz, 16 Hz or 17 Hz, etc.), and the kneading time of the first kneading is independently 2 to 3 min (for example, 2.1 min, 2.2 min, 2.3 min, 2.4 min, 2.5 min, 2.6 min, 2.7 min, 2.8 min or 2.9 min, etc.).

[0039] Preferably, the second kneading in step (2), step (3) and step (4) is carried out under vacuum, the kneading frequency of the second kneading is independently 20 to 30 Hz (for example, 21 Hz, 22 Hz, 23 Hz, 24 Hz, 25 Hz, 26 Hz, 27 Hz, 28 Hz or 29 Hz, etc.), and the kneading time of the second kneading is independently 10 to 30 min (for example, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min or 28 min, etc.).

[0040] In a third aspect, the present invention provides a use of the thermally conductive insulating gasket as described in the first aspect as a heat dissipation material.

[0041] In the present invention, the thermally conductive insulating gasket can be used as a heat dissipation material in the fields of 5G communication base stations, wireless infrastructure, optical modules, precision optoelectronics, automotive electronic device heat dissipation, automotive power batteries, hard disk drives or solid-state hard disk storage devices; and can be used for heat dissipation connection between heat-generating components and radiators or housings.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] The thermally conductive insulating gasket prepared by compounding double-ended vinyl silicone oil, hydrogenated silicone oil, inhibitor, long-chain silane coupling agent, catalyst, submicron single crystal alumina, aluminum nitride fiber, spherical alumina and diamond powder in the present invention has the characteristics of high thermal conductivity, high tear strength and insulation, so that the thermally conductive insulating gasket is not easy to be torn, and even a thin sheet of 0.3 to 0.8 mm can be well operated and used. The thermal conductivity of the thermally conductive insulating gasket is ≥14.3W·m -1 K -1 , tear strength is ≥0.2MPa. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0045] The sources of some components in the following examples and comparative examples are as follows:

[0046] Double-terminated vinyl silicone oil: vinyl content of 0.35-0.6wt%, viscosity of 50-120mPa.s at 25°C, commercially available, the same commercial product was used in parallel experiments;

[0047] Double-terminal hydrogenated silicone oil: hydrogen content of 0.18 wt%, viscosity of 20-40 mPa.s at 25°C, commercially available, the same commercially available product was used in parallel experiments;

[0048] Side hydrogen-containing silicone oil: hydrogen content is 0.1wt%, viscosity is 50-80mPa.s at 25°C, commercially available, and the same commercial product was used in parallel experiments;

[0049] Inhibitor: ethynylcyclohexanol, commercially available, the same commercial product was used in parallel experiments;

[0050] Catalyst: Platinum catalyst, a platinum complex made with divinyltetramethyldisiloxane as a ligand, commercially available, and the same commercial product was used in parallel experiments.

[0051] Example 1

[0052] The present embodiment provides a thermally conductive insulating gasket and a preparation method thereof, wherein the raw materials for preparing the thermally conductive insulating gasket include the following components by weight: 25 parts of double-ended vinyl silicone oil, 0.26 parts of double-ended hydrogenated silicone oil, 0.8 parts of side hydrogenated silicone oil, 0.06 parts of inhibitor, 2.8 parts of long-chain silane coupling agent (n-decyltrimethoxysilane), 0.24 parts of catalyst, 130 parts of submicron single crystal alumina (D50 particle size is 0.5 μm), and aluminum nitride fiber (diameter The present invention relates to a first spherical alumina (D50 particle size is 10 μm, length is 2 mm) 120 parts, a first spherical alumina (D50 particle size is 5 μm) 45 parts, a second spherical alumina (D50 particle size is 50 μm) 100 parts, a third spherical alumina (D50 particle size is 100 μm) 160 parts, a first diamond powder (D50 particle size is 8 μm) 56 parts, a second diamond powder (D50 particle size is 35 μm) 80 parts and a third diamond powder (D50 particle size is 120 μm) 155 parts.

[0053] The preparation method of the preparation method comprises the following steps:

[0054] (1) adding bi-terminal vinyl silicone oil, bi-terminal hydrogen silicone oil, side hydrogen silicone oil, inhibitor, long-chain silane coupling agent and catalyst into a kneader in sequence, turning on the kneader to knead in forward rotation for a first kneading, setting the kneading frequency of the first kneading to 35 Hz, and the kneading time to 5 min, and then performing a second kneading under vacuum, setting the kneading frequency of the second kneading to 35 Hz, and the kneading time to 5 min, to obtain a first mixture;

[0055] (2) adding submicron single crystal alumina, aluminum nitride fiber, first spherical alumina and first diamond powder to the first mixture obtained in step (1) for first kneading, setting the kneading frequency of the first kneading to 18 Hz and the kneading time to 2 min, and then performing a second kneading under vacuum, setting the kneading frequency of the second kneading to 30 Hz and the kneading time to 10 min, to obtain a second mixture;

[0056] (3) adding the second spherical alumina and the second diamond powder to the second mixture obtained in step (2) to perform a first kneading, wherein the kneading frequency of the first kneading is set to 18 Hz and the kneading time is set to 2 min, and then performing a second kneading under vacuum, wherein the kneading frequency of the second kneading is set to 30 Hz and the kneading time is set to 10 min, to obtain a third mixture;

[0057] (4) performing a first kneading on the third mixture obtained in step (3), the third spherical alumina and the third diamond powder, wherein the kneading frequency of the first kneading is set to 18 Hz and the kneading time is set to 2 min, and then performing a second kneading under vacuum, wherein the kneading frequency of the second kneading is set to 30 Hz and the kneading time is set to 10 min, to obtain a fourth mixture;

[0058] (5) The fourth mixture obtained in step (4) is rolled into a sheet by a rolling machine, and then baked in a tunnel furnace at 120° C. for 30 minutes for vulcanization molding to obtain the thermally conductive insulating gasket.

[0059] Example 2

[0060] The present embodiment provides a thermally conductive insulating gasket and a preparation method thereof. The raw materials for preparing the thermally conductive insulating gasket include the following components by weight: 30 parts of double-ended vinyl silicone oil, 0.32 parts of double-ended hydrogenated silicone oil, 0.96 parts of side hydrogenated silicone oil, 0.08 parts of inhibitor, 2.5 parts of long-chain silane coupling agent (dodecyltrimethoxysilane), 0.3 parts of catalyst, 160 parts of submicron single crystal alumina (D50 particle size is 0.6 μm), aluminum nitride fiber ( Diameter is 5μm, length is 1mm) 180 parts, first spherical alumina (D50 particle size is 2μm) 60 parts, second spherical alumina (D50 particle size is 55μm) 100 parts, third spherical alumina (D50 particle size is 80μm) 232 parts, first diamond powder (D50 particle size is 5μm) 40 parts, second diamond powder (D50 particle size is 25μm) 30 parts and third diamond powder (D50 particle size is 90μm) 200 parts.

[0061] The preparation method of the preparation method comprises the following steps:

[0062] (1) adding bi-terminal vinyl silicone oil, bi-terminal hydrogen silicone oil, side hydrogen silicone oil, inhibitor, long-chain silane coupling agent and catalyst into a kneader in sequence, turning on the kneader to knead in forward rotation for a first kneading, setting the kneading frequency of the first kneading to 30 Hz, and the kneading time to 8 min, and then performing a second kneading under vacuum, setting the kneading frequency of the second kneading to 30 Hz, and the kneading time to 8 min, to obtain a first mixture;

[0063] (2) adding submicron single crystal alumina, aluminum nitride fiber, first spherical alumina and first diamond powder to the first mixture obtained in step (1) for first kneading, setting the kneading frequency of the first kneading to 15 Hz and the kneading time to 3 min, and then performing a second kneading under vacuum, setting the kneading frequency of the second kneading to 25 Hz and the kneading time to 15 min, to obtain a second mixture;

[0064] (3) adding the second spherical alumina and the second diamond powder to the second mixture obtained in step (2) to perform a first kneading, wherein the kneading frequency of the first kneading is set to 15 Hz and the kneading time is set to 3 min, and then performing a second kneading under vacuum, wherein the kneading frequency of the second kneading is set to 25 Hz and the kneading time is set to 15 min, to obtain a third mixture;

[0065] (4) performing a first kneading on the third mixture obtained in step (3), the third spherical alumina and the third diamond powder, wherein the kneading frequency of the first kneading is set to 15 Hz and the kneading time is set to 3 min, and then performing a second kneading under vacuum, wherein the kneading frequency of the second kneading is set to 25 Hz and the kneading time is set to 15 min, to obtain a fourth mixture;

[0066] (5) The fourth mixture obtained in step (4) is rolled into a sheet by a rolling machine, and then baked in a tunnel furnace at 120° C. for 30 minutes for vulcanization molding to obtain the thermally conductive insulating gasket.

[0067] Example 3

[0068] The present embodiment provides a thermally conductive insulating gasket and a preparation method thereof. The raw materials for preparing the thermally conductive insulating gasket include the following components by weight: 23 parts of double-ended vinyl silicone oil, 0.25 parts of double-ended hydrogenated silicone oil, 0.75 parts of side hydrogenated silicone oil, 0.05 parts of inhibitor, 2.9 parts of long-chain silane coupling agent (n-decyltrimethoxysilane), 0.2 parts of catalyst, 90 parts of submicron single crystal alumina (D50 particle size is 0.4 μm), and aluminum nitride fiber (diameter is 2 0μm, length 3mm), 60 parts of the first spherical alumina (D50 particle size is 8μm), 120 parts of the second spherical alumina (D50 particle size is 35μm), 110 parts of the third spherical alumina (D50 particle size is 130μm), 100 parts of the first diamond powder (D50 particle size is 10μm), 160 parts of the second diamond powder (D50 particle size is 45μm) and 188 parts of the third diamond powder (D50 particle size is 150μm).

[0069] The preparation method of the preparation method comprises the following steps:

[0070] (1) adding bi-terminal vinyl silicone oil, bi-terminal hydrogen silicone oil, side hydrogen silicone oil, inhibitor, long-chain silane coupling agent and catalyst into a kneader in sequence, turning on the kneader to knead in forward rotation for a first kneading, setting the kneading frequency of the first kneading to 25 Hz, and the kneading time to 10 min, and then performing a second kneading under vacuum, setting the kneading frequency of the second kneading to 25 Hz, and the kneading time to 10 min, to obtain a first mixture;

[0071] (2) adding submicron single crystal alumina, aluminum nitride fiber, first spherical alumina and first diamond powder to the first mixture obtained in step (1) for first kneading, setting the kneading frequency of the first kneading to 12 Hz and the kneading time to 3 min, and then performing a second kneading under vacuum, setting the kneading frequency of the second kneading to 20 Hz and the kneading time to 30 min, to obtain a second mixture;

[0072] (3) adding the second spherical alumina and the second diamond powder to the second mixture obtained in step (2) to perform a first kneading, wherein the kneading frequency of the first kneading is set to 12 Hz and the kneading time is set to 3 min, and then performing a second kneading under vacuum, wherein the kneading frequency of the second kneading is set to 20 Hz and the kneading time is set to 30 min, to obtain a third mixture;

[0073] (4) performing a first kneading on the third mixture obtained in step (3), the third spherical alumina and the third diamond powder, wherein the kneading frequency of the first kneading is set to 12 Hz and the kneading time is set to 3 min, and then performing a second kneading under vacuum, wherein the kneading frequency of the second kneading is set to 20 Hz and the kneading time is set to 30 min, to obtain a fourth mixture;

[0074] (5) The fourth mixture obtained in step (4) is rolled into a sheet by a rolling machine, and then baked in a tunnel furnace at 120° C. for 30 minutes for vulcanization molding to obtain the thermally conductive insulating gasket.

[0075] Example 4

[0076] The present embodiment provides a thermally conductive insulating gasket and a preparation method thereof, which differs from Example 1 only in that the first spherical alumina (D50 particle size is 5 μm) is not added, and the weight portions of the second spherical alumina (D50 particle size is 50 μm) and the third spherical alumina (D50 particle size is 100 μm) are increased proportionally, a total of 45 portions, and other conditions are the same as Example 1.

[0077] Example 5

[0078] The present embodiment provides a thermally conductive insulating gasket and a preparation method thereof, which differs from Example 1 only in that the second spherical alumina (D50 particle size is 50 μm) is not added, and the weight portions of the first spherical alumina (D50 particle size is 5 μm) and the third spherical alumina (D50 particle size is 100 μm) are increased proportionally, with a total increase of 100 portions, and other conditions are the same as those in Example 1.

[0079] Example 6

[0080] The present embodiment provides a thermally conductive insulating gasket and a preparation method thereof, which differs from Example 1 only in that the third spherical alumina (D50 particle size is 100 μm) is not added, and the weight portions of the first spherical alumina (D50 particle size is 5 μm) and the second spherical alumina (D50 particle size is 50 μm) are increased proportionally, a total of 160 portions, and other conditions are the same as Example 1.

[0081] Example 7

[0082] This embodiment provides a thermally conductive insulating gasket and a preparation method thereof, which differs from Embodiment 1 only in that the first diamond powder (D50 particle size is 8 μm) is not added, and the weight portions of the second diamond powder (D50 particle size is 35 μm) and the third diamond powder (D50 particle size is 120 μm) are increased proportionally, a total of 56 portions, and other conditions are the same as Embodiment 1.

[0083] Example 8

[0084] This embodiment provides a thermally conductive insulating gasket and a preparation method thereof, which differs from Embodiment 1 only in that the second diamond powder (D50 particle size is 35 μm) is not added, and the weight portions of the first diamond powder (D50 particle size is 8 μm) and the third diamond powder (D50 particle size is 120 μm) are increased proportionally, a total of 80 portions, and other conditions are the same as Embodiment 1.

[0085] Example 9

[0086] This embodiment provides a thermally conductive insulating gasket and a preparation method thereof, which differs from Embodiment 1 only in that the third diamond powder (D50 particle size is 120 μm) is not added, and the weight portions of the first diamond powder (D50 particle size is 8 μm) and the second diamond powder (D50 particle size is 35 μm) are increased proportionally, a total of 155 portions, and other conditions are the same as Embodiment 1.

[0087] Comparative Example 1

[0088] This embodiment provides a thermally conductive insulating gasket and a preparation method thereof. The only difference between this embodiment and Embodiment 1 is that the weight fraction of aluminum nitride fiber (with a diameter of 20 μm and a length of 3 mm) is adjusted to 40 parts, and other conditions are the same as those in Embodiment 1.

[0089] Comparative Example 2

[0090] This comparative example provides a thermally conductive insulating gasket and a preparation method thereof, which differs from Example 1 only in that the submicron single crystal alumina (D50 particle size is 0.5 μm) is replaced with spherical alumina (D50 particle size is 0.5 μm) of the same mass, and other conditions are the same as Example 1.

[0091] Comparative Example 3

[0092] This comparative example provides a thermally conductive insulating gasket and a preparation method thereof, which differs from Example 1 only in that the first diamond powder (D50 particle size is 8 μm) is replaced by the same mass of the first spherical boron nitride (D50 particle size is 8 μm); the second diamond powder (D50 particle size is 35 μm) is replaced by the same mass of the second spherical boron nitride (D50 particle size is 35 μm); the third diamond powder (D50 particle size is 120 μm) is replaced by the same mass of the third spherical boron nitride (D50 particle size is 120 μm), and other conditions are the same as those in Example 1.

[0093] Comparative Example 4

[0094] This comparative example provides a thermally conductive insulating gasket and a preparation method thereof, which differs from Example 1 only in that the aluminum nitride fiber (diameter of 10 μm, length of 2 mm) is replaced with spherical alumina of the same mass (D50 particle size of 10 μm), and other conditions are the same as Example 1.

[0095] Comparative Example 5

[0096] This comparative example provides a thermally conductive insulating gasket and a preparation method thereof, which differs from Example 1 only in that the first diamond powder (D50 particle size is 8 μm) is replaced by the same mass of spherical alumina (D50 particle size is 8 μm), the second diamond powder (D50 particle size is 35 μm) is replaced by the same mass of spherical alumina (D50 particle size is 35 μm), and the third diamond powder (D50 particle size is 120 μm) is replaced by the same mass of spherical alumina (D50 particle size is 120 μm). Other conditions are the same as those in Example 1.

[0097] Comparative Example 6

[0098] This comparative example provides a thermally conductive insulating gasket and a preparation method thereof, which is different from Example 1 only in that no long-chain silane coupling agent is added, and other conditions are the same as Example 1.

[0099] The following performance tests were performed on the thermally conductive insulating gaskets provided in the above Examples 1 to 9 and Comparative Examples 1 to 6:

[0100] Thermal conductivity: Tested in accordance with ASTM D5470-2012, the test sample thickness of the thermally conductive insulating gasket is 2.0 mm.

[0101] Tear strength: tested in accordance with ASTM D412-2006, the test sample thickness of the thermally conductive insulating gasket is 6 mm.

[0102] Hardness: Tested in accordance with ASTM D2240-2015.

[0103] The test results are shown in Table 1 below:

[0104] Table 1

[0105]

[0106]

[0107] In Table 1, “ / ” means that the result was not measured.

[0108] From the content of Table 1, it can be seen that the thermal conductivity of the thermally conductive insulating gaskets provided in Examples 1 to 9 is 14.3 to 17.2 W·m -1 K -1 , tear strength ≥0.2MPa.

[0109] Compared with Example 1, if the first spherical alumina is not added, and the spherical alumina is a combination of the second spherical alumina and the third spherical alumina (Example 4), the thermal conductivity of the prepared thermally conductive insulating gasket is reduced; if the second spherical alumina is not added, and the spherical alumina is a combination of the first spherical alumina and the third spherical alumina (Example 5), the thermal conductivity of the prepared thermally conductive insulating gasket is reduced; if the third spherical alumina is not added, and the spherical alumina is a combination of the first spherical alumina and the second spherical alumina (Example 6), the thermal conductivity of the prepared thermally conductive insulating gasket is reduced; it can be seen that in the present invention, by adopting a combination of spherical aluminas with three different D50 particle sizes, the prepared thermally conductive insulating gasket has better performance.

[0110] Compared with Example 1, if the first diamond powder is not added, and the diamond powder is a combination of the second diamond powder and the third diamond powder (Example 7), the thermal conductivity of the prepared thermally conductive insulating gasket is reduced; if the second diamond powder is not added, and the diamond powder is a combination of the first diamond powder and the third diamond powder (Example 8), the thermal conductivity of the prepared thermally conductive insulating gasket is reduced; if the third diamond powder is not added, and the diamond powder is a combination of the first diamond powder and the second diamond powder (Example 9), the thermal conductivity of the prepared thermally conductive insulating gasket is reduced; it can be seen that in the present invention, by using a combination of three diamond powders with different D50 particle sizes, the performance of the prepared thermally conductive insulating gasket is better.

[0111] Compared with Example 1, if the weight percentage of aluminum nitride fiber is too low (Comparative Example 1), the thermal conductivity and tear strength of the prepared thermally conductive insulating gasket are reduced. It can be seen that the performance of the thermally conductive insulating gasket prepared by controlling the weight percentage of aluminum nitride fiber within a specific range is better.

[0112] Compared with Example 1, if the submicron single crystal alumina (D50 particle size is 0.5 μm) is replaced by spherical alumina (D50 particle size is 0.5 μm) (Comparative Example 2), the thermal conductivity of the prepared thermally conductive insulating gasket is reduced. It can be seen that the thermally conductive insulating gasket prepared by combining submicron single crystal alumina, aluminum nitride fiber, spherical alumina and diamond powder as inorganic thermally conductive powder in the present invention has better performance.

[0113] Compared with Example 1, if the diamond powder is replaced with spherical boron nitride (Comparative Example 3), the spherical boron nitride is severely thickened and cannot be added to achieve uniform mixing, so the thermally conductive insulating gasket cannot be prepared.

[0114] Compared with Example 1, if the aluminum nitride fiber is replaced with spherical aluminum oxide (Comparative Example 4), the thermal conductivity and tear strength of the prepared thermally conductive insulating gasket are both lower.

[0115] Compared with Example 1, if the diamond powder is replaced with spherical alumina (Comparative Example 5), the thermal conductivity of the prepared thermally conductive insulating gasket is significantly lower.

[0116] Compared with Example 1, if the long-chain silane coupling agent is not added (Comparative Example 6), the inorganic thermally conductive powder has poor compatibility with the double-ended vinyl silicone oil and hydrogenated silicone oil, poor dispersion effect, and the thermal conductivity and tear strength of the prepared thermally conductive insulating gasket are both low.

[0117] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate a thermally conductive insulating gasket and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A thermally conductive insulating gasket, characterized in that: The raw materials for preparing the thermally conductive insulating gasket include the following components in parts by weight: 23-30 parts of double-ended vinyl silicone oil, 1-4 parts of hydrogen-containing silicone oil, 0.05-0.2 parts of inhibitor, 1-6 parts of long-chain silane coupling agent, 0.1-0.5 parts of catalyst, 80-160 parts of submicron single crystal alumina, 60-180 parts of aluminum nitride fiber, 300-400 parts of spherical alumina and 280-480 parts of diamond powder.

2. The thermally conductive insulating gasket according to claim 1, characterized in that: The hydrogen-containing silicone oil includes double-end hydrogen-containing silicone oil and side hydrogen-containing silicone oil; Preferably, the mass ratio of the double-ended hydrogen-containing silicone oil to the side hydrogen-containing silicone oil is 1:(2.8-3.2); Preferably, the inhibitor comprises an alkynol inhibitor; Preferably, the long-chain silane coupling agent includes n-decyltrimethoxysilane and / or dodecyltrimethoxysilane; Preferably, the catalyst comprises a platinum catalyst.

3. The thermally conductive insulating gasket according to claim 2 or 3, characterized in that: The D50 particle size of the submicron single crystal aluminum oxide is 0.4 to 0.6 μm; Preferably, the aluminum nitride fiber has a diameter of 5 to 20 μm and a length of 1 to 3 mm.

4. The thermally conductive insulating gasket according to any one of claims 1 to 3, characterized in that: The spherical alumina comprises a combination of a first spherical alumina, a second spherical alumina and a third spherical alumina, the D50 particle size of the first spherical alumina is 2 to 8 μm, the D50 particle size of the second spherical alumina is 35 to 55 μm, and the D50 particle size of the third spherical alumina is 80 to 130 μm; Preferably, the mass ratio of the first spherical alumina, the second spherical alumina and the third spherical alumina is 1:(0.5-3):(1-5).

5. The thermally conductive insulating gasket according to any one of claims 1 to 4, characterized in that: The diamond powder comprises a combination of a first diamond powder, a second diamond powder and a third diamond powder, wherein the D50 particle size of the first diamond powder is 5 to 10 μm, the D50 particle size of the second diamond powder is 20 to 45 μm, and the D50 particle size of the third diamond powder is 90 to 150 μm; Preferably, the mass ratio of the first diamond powder, the second diamond powder and the third diamond powder is 1:(0.5-3):(1-5).

6. The thermally conductive insulating gasket according to any one of claims 1 to 5, characterized in that: The raw materials for preparing the thermally conductive insulating gasket also include color paste; Preferably, the weight portion of the color paste in the raw materials for preparing the thermally conductive insulating gasket is 0.1 to 1 part; Preferably, the thickness of the thermally conductive insulating gasket is 0.3-10 mm.

7. A method for preparing a thermally conductive insulating gasket according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: kneading, rolling and vulcanizing double-ended vinyl silicone oil, hydrogen-containing silicone oil, inhibitor, long-chain silane coupling agent, catalyst, submicron single crystal alumina, aluminum nitride fiber, spherical alumina and diamond powder to obtain the thermally conductive insulating gasket.

8. The method for preparing a thermally conductive insulating gasket according to claim 7, characterized in that: The preparation method specifically comprises the following steps: (1) performing a first kneading and a second kneading of a double-terminal vinyl silicone oil, a hydrogen-containing silicone oil, an inhibitor, a long-chain silane coupling agent and a catalyst to obtain a first mixture; (2) performing a first kneading and a second kneading on the first mixture obtained in step (1), the submicron single crystal aluminum oxide, the aluminum nitride fiber, the first spherical aluminum oxide and the first diamond powder to obtain a second mixture; (3) subjecting the second mixture obtained in step (2), the second spherical alumina, and the second diamond powder to a first kneading and a second kneading to obtain a third mixture; (4) subjecting the third mixture obtained in step (3), the third spherical alumina, the third diamond powder and optionally the color paste to a first kneading and a second kneading to obtain a fourth mixture; (5) The fourth mixture obtained in step (4) is rolled and vulcanized to obtain the thermally conductive insulating gasket.

9. The preparation method according to claim 8, characterized in that: Step (1) The kneading frequency of the first kneading is 25 to 35 Hz, and the kneading time of the first kneading is 5 to 10 min; Preferably, the second kneading in step (1) is carried out under vacuum, the kneading frequency of the second kneading is 25 to 35 Hz, and the kneading time of the second kneading is 5 to 10 min; Preferably, the kneading frequency of the first kneading in step (2), step (3) and step (4) is independently 12 to 18 Hz, and the kneading time of the first kneading is independently 2 to 3 min; Preferably, the second kneading in step (2), step (3) and step (4) is carried out under vacuum, the kneading frequency of the second kneading is independently 20 to 30 Hz, and the kneading time of the second kneading is independently 10 to 30 min.

10. Use of the thermally conductive insulating gasket according to any one of claims 1 to 6 as a heat dissipation material.

Citation Information

Patent Citations

  • Heat-conducting silica gel gasket and preparation method thereof

    CN117924776A